2015
DOI: 10.1590/1983-084x/14_074
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and repellent activity of the essential oil of Cinnamomum camphora var. linaloolifera Y. Fujita (Ho-Sho) and Cinnamomum camphora (L.) J Presl. var. hosyo (Hon-Sho) on Sitophilus zeamaisMots. (Coleoptera, Curculionedae)

Abstract: Recebido para publicação em 11/07/2014 Aceito para publicação em 02/12/2014 Sul, Rua Francisco Getulio Vargas, 1130, Caxias do Sul, RS 95070-560. 3 Universidade Federal Fronteira Sul, Av. Dom João Hoffmann, 313, Erechim, RS, 99700-000.*Corresponding Author: cansian@uricer.edu.br ABSTRACT: The aim of this work was to evaluate the insecticidal and repellency activity of the essential oil of Cinnamomum camphora var. linaloolifera Y. Fujita (Ho-Sho) and Cinnamomum camphora (L.) J Presl.var. hosyo (Hon-Sho), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Relative to C. camphora essential oil, other authors reported similar results, which also characterized linalool as the major compound of this essential oil in contents ranging from 84 to 95 wt.% (Cansian et al, 2010(Cansian et al, , 2015Nenaah & Ibrahim, 2011;Tomazoni et al, 2017).…”
Section: Essential Oil Yield and Compositionmentioning
confidence: 67%
See 2 more Smart Citations
“…Relative to C. camphora essential oil, other authors reported similar results, which also characterized linalool as the major compound of this essential oil in contents ranging from 84 to 95 wt.% (Cansian et al, 2010(Cansian et al, , 2015Nenaah & Ibrahim, 2011;Tomazoni et al, 2017).…”
Section: Essential Oil Yield and Compositionmentioning
confidence: 67%
“…Literature is scarce about the effect of the essential oil of C. camphora in the juvenile phase (eggs and nymphs) of T. vaporariorum, neither other species, having only studies relative to the adult phase. The essential oil of C. camphora has had toxicity on Sitophilus zeamais, causing 100% mortality at the concentration of 0.114% v/v (Cansian et al, 2015).…”
Section: Insecticidal Activity Of C Camphora Essential Oil On T Vaporariorummentioning
confidence: 99%
See 1 more Smart Citation
“…계피정유는 주로 수증기증류법(steam distillation)으로 추출되 어지며 이들의 주요성분으로는 모노테르펜으로서 cinnamaldehyde 가 약 92% 정도 존재하는 것으로 보고되었다 [5]. 이 계피 정유 의 항균작용으로는 균 세포안의 전해질의 누설현상 유도 및 대 사작용의 저하로서 확인되었으며 [5], 이러한 항균작용과 더불어 옥수수바구미(Sitophilus zeamais)에 대한 살충 및 기피작용을 나 타내었다 [6]. 살충효과는 농업해충에서도 발견되었으며 실험에 사용된 농업해충으로는 복숭아혹진딧물(Myzus persicae), 배추좀 나방(Plutella xylostella), 및 점박이 응애(Tetranychus urticae) 등이었다 [7].…”
Section: 서 론unclassified
“…Al respecto, (Müller et al 2009), S. zeamais (Cansian et al 2015), Plutella xylostella (L.) (Plutellidae) (Mao-xin et al 2004) y Lycorma delicatula (White) (Fulgoridae) (Yoon et al 2011).…”
Section: Concentración (%)mentioning
confidence: 99%